NUTRIÇÃO MINERAL DA PARTE ÁEREA EM PLANTAS DE STRELITZIA AUGUSTA SOB DEFICIÊNCIAS DE MACRONUTRIENTES - COELHO, Viviane Amaral Toledo; SOUZA, Carla Giselly de; NASCIMENTO, Ednardo de Souza; LACERDA, Luiza Gobira; CARDOSO, Patrícia Alves (Brazilian Journal of Biometrics, 2020)
The aim of this study was to evaluate the dry matter production and mineral nutrition of Strelitzia augusta under macronutrient deficiencies. The experimental design was completely randomized with seven treatments and three replications. The treatments were: complete nutrient solution and nutrient solutions with individual omissions of N, P, K, Ca, Mg and S. After adaptation, the plants were selected for size uniformity and transplanted to 100% nutrient solution plastic pots. The plants were harvested, the material dried and weighed to obtain the dry matter mass and milled for chemical analysis. The dry matter production, contents and accumulations of the plant area of Strelitizia augusta were affected by the different omissions and showed statistical differences among them. In the beginning, nutritional deficiency causes a change at the cellular level, resulting in a visual change and in the physiology (levels and accumulations) of Strelitzia augusta plants. The omission of macronutrients affects the dry matter production of shoots of Strelitzia augusta. Deficiencies in macronutrients cause changes in the levels and accumulations in the shoots of Strelitzia augusta.